Analysis of Work Discipline and Work Competence on Employee Performance at PT. Parkland World Indonesia - Hartoko, Gatot; Noviyanti, Eka Sintia; Saleh, Muhamad; Fatari, Fatari; Hidayat, Ardi; Bahits, Abdul (LPPM Universitas Bina Bangsa, 2021)
This study aims to determine how much influence the work discipline and work competence have on employee performance in the department development department of PT. Parkland World Indonesia Serang. This study uses a quantitative approach using a survey method with a saturated sample whose population is sampled as all 40 respondents. The analysis technique used is multiple linear regression analysis, correlations, T-test, F test, and coefficient of determination. The study work discipline variables and work competence have a significant partial effect on employee performance. Evidenced by the magnitude of the work discipline regression coefficient of 0.546 and work competence of 0.518 with a significant value of 0,000 (0,000 <0.05). Simultaneously a significant effect on employee performance, evidenced by Tcount>Ttable or 35,071> 3,250. Partially the comparison of t-count and t-table shows the work discipline variable Tcount>Ttable or 4,478> 2,026 and the work competency variable Tcount>Ttable or 4,848> 2,026. The coefficient of determination obtained by 65.5% of employee performance, the remaining 34.5% is influenced by other variables that are not meticulous such as motivation, leadership style, and others